Perceived Organizational Support, OCB and Creative Behaviour among Millennial Generation Start-up Employees - erika setyanti kusumaputri; sitta Puteri Kumalasari; Sabiqotul Husna (Journal of Educational, Health and Community Psychology, 2021)
Millennial generation employees were expected to have the ability to create and innovate. This ability will lead to creative behaviour particularly when companies support employee welfare which was strengthened by organizational citizenship behaviour (OCB). The purpose of this study was to investigate the relationship between organizational citizenship behaviour as a mediator of perceived organizational support (POS) for creative behaviour. The number of research participants was 157 millennial generation employees from Indonesian start-up companies. Data were collected using the creative behaviour scale (α = 0.887), the POS scale (α = 0.945), and the OCB scale (α = 0.951). The results of the study based on the path analysis method showed that the indirect effect had a coefficient of 0.339 (p <0.05), which means that there was a positive relationship between POS and creative behaviour through OCB. The positive sign on the correlation coefficient showed the direction of a positive relationship, which means that the higher the POS employees have, the higher the employee's creative behaviour through OCB. OCB as a mediator contributed 46.4% to POS towards creative behaviour.Keywords: millennial generation, organizational citizenship behaviour,                               perceived organizational support, creative behaviour